Assessment of Contingency Sum in Buying of Offshore Construction Materials and Its Impact on Total Project Cost to Improve the Inventory Management: A Case Study PT SATM - Veren Priscila; Rhea D. Casela; Nicole Joy M. Realingo (Universitas Atma Jaya Yogyakarta, 2025)
This study examines the operational challenges faced by an offshore company that has specialized in rigs and floaters, repairs and upgrades, offshore platforms, and specialized shipbuilding over the past seven years. Despite steady growth, the company has encountered significant issues related to contingency fund management during the construction phase. To mitigate unpredictable risk exposure, the company applies a 20% contingency to the total cost estimate of every offshore construction material. However, this approach has led to a consistent 10% surplus, resulting in excessive costs and inventory. The research aims to evaluate the effectiveness of the current contingency allocation strategy and propose solutions to reduce surplus costs and excess inventory. By analyzing the company's data, the study identifies key inefficiencies and suggests optimized approaches to contingency fund management. The findings aim to provide actionable insights for enhancing financial and inventory management practices, ultimately improving the company's overall operational efficiency and profitability.